Effects of dietary protected fat and vitamin E on in vitro rumen fermentation characteristics and reproductive performances of Hanwoo cows - Young Ho Joo; Chang Hyun Baeg; Ji Yoon Kim; Bu Gil Choi; Dimas Hand Vidya Paradhipta; Dong Hyeon Kim; Seong Shin Lee; Sam Churl Kim (Journal of Animal Science and Technology)
The present study investigated the effects of protected dietary fat and vitamin E on the reproductive performances of Hanwoo during the estrus period. The present study consisted of two experiments. Experiment 1 determined the effects of dietary supplements on the in vitro nutrient digestibility and fermentation characteristics in the rumen. Experiment 2 determined the effects of dietary supplements on blood fatty acid profiles, blood metabolites, and the pregnancy rate of Hanwoo cows. The basal diet was a total mixed ration, which was formulated for Hanwoo cows and was treated with different supplements as follows: without supplement (CON); supplemented 1% of protected fat (PF); supplemented 1% vitamin E (VE); and mixed PF and VE at 1:1 (MIX) based on dry matter (DM). The experimental diets were incubated in the rumen buffer for 72 h at 39°C with four replications and three blanks for Experiment 1. In Experiment 2, forty Hanwoo cows on estrus (2.7 ± 0.15 of parity) were assigned to each dietary treatment. Each treatment consisted of ten Hanwoo cows placed in two pens and fed individually (5 steers per pen). The feeding period was conducted for 75 days, from 30 d before to 45 d after artificial insemination (AI). In Experiment 1, dietary treatment did not affect nutrient digestibility or fermentation characteristics in the rumen except for the concentration of total volatile fatty acid (VFA). Dietary PF had a higher (p < 0.05) total VFA concentration than CON. In Experiment 2, dietary PF and MIX had higher (p < 0.05) saturated fatty acid concentrations in the blood of Hanwoo cows, while dietary VE and MIX had higher (p < 0.05) vitamin E concentrations. Estrogen concentrations in the blood of Hanwoo cows were lower (p < 0.05) in all treatments with supplementary diets. All treatments with supplementary diets had lower (p < 0.05) AI numbers, resulting in a higher pregnancy rate (p < 0.05) of Hanwoo cows. The present study found that the single and combo supplements with PF and vitamin E had beneficial effects on the reproductive performances of Hanwoo cows on estrus.